BAKTERI KONTAMINAN Salmonella sp. PADA KECOA (Blattidae) DI KAPAL DOMESTIK YANG BERSANDAR DI PELABUHAN PANGKALBALAM KEPULAUAN BANGKA BELITUNG Contaminant Bacteria Salmonella sp. on Cockroachs (Blattidae) in Domestic’s Ship in Pangkalbalam’s Port Bangka Belitung Island - Fitriana Dwi Fidiawati; Retno Hestiningsih; Martini Martini; Praba Ginandjar (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2017)
Cockroach is a vector which is often found on the ship that can affect the condition of crew, because cockroach spreads diseases to humans through pathogenic bacteria. Data showed that 10,5% of ships in Pangkalbalam’s Port had bad sanitation which cause the ships as the area where this vector do reproduction. The objective of this study was to identify the contaminant bacteria Salmonella sp. from the cockroach’s external body in domestic ship in Pangkalbalam’s Port. This was an explanatory research with cross sectional approach. Populations of this research were all cockroaches on domestic’s ship (cargo, passenger, tugboat, and tanker). Samples of this research were taken purposively which represent the species and sex of the cockroach from four different places (kitchen, pantry, crew’s room, and passenger’s room). Laboratory experiment resulted from among 30 cockroaches, 3,3% positively infected by Salmonella enteritidis with total bacteria on each cockroach was 3,7 x 106colony/gr. Crew have to keep personal hygiene and sanitation of ship to reduce cockroach population.